The Impact of Infrastructure on Economic Growth in West Sumatra: A Dynamic Panel Analysis - Putra, Voby Vandeska; Maryati, Sri (SAFE-Network, 2026)
This study investigates the effects of basic infrastructure, educational infrastructure, and the Human Development Index (HDI) on district and municipal economic growth in West Sumatra Province, Indonesia. The analysis encompasses road infrastructure, access to clean water, electricity, telecommunications, and educational participation from primary to senior secondary levels, with HDI serving as a proxy for human capital. Panel data covering 19 districts and municipalities over the period 2015–2024 are employed, obtained from Statistics Indonesia. To control for endogeneity, unobserved heterogeneity, and growth dynamics, the model is estimated using the two-step dynamic panel System Generalized Method of Moments (System GMM). The findings reveal strong growth persistence, indicating that current regional economic performance is significantly shaped by past outcomes. Primary and senior secondary educational infrastructure, together with HDI, exert positive and statistically significant effects on economic growth. Conversely, water infrastructure shows a negative and significant association, while road infrastructure displays a negative but insignificant relationship. Electricity, telecommunications, and junior secondary education infrastructure present positive yet statistically insignificant effects. These results suggest that infrastructure expansion alone is insufficient to stimulate economic growth; its effectiveness critically depends on service quality, utilization efficiency, and complementarities with human capital. This study contributes empirical evidence on heterogeneous infrastructure effects in subnational dynamic panel settings and underscores the importance of integrating infrastructure quality improvements with human capital development to achieve sustainable and inclusive regional growth.